2016
DOI: 10.1038/srep28460
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nuclear Actin in HDAC 1 and 2 Regulation

Abstract: Class I histone deacetylases (HDACs) are known to remove acetyl groups from histone tails. This liberates positive charges on the histone tail and allows for tighter winding of DNA, preventing transcription factor binding and gene activation. Although the functions of HDAC proteins are becoming apparent both biochemically and clinically, how this class of proteins is regulated remains poorly understood. We identified a novel interaction between nuclear actin and HDAC 1 and HDAC 2. Nuclear actin has been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 52 publications
5
45
0
Order By: Relevance
“…Similarly, depleting nuclear actin through changes in growth factors or extracellular molecules has been reported to inhibit RNAPII activity, and this inhibition can be rescued by expressing NLS-R62D-β-actin (Spencer et al, 2011). These data, which support the notion that monomeric actin is important in maintaining transcription, are consistent with the previous demonstration that monomeric nuclear actin interacts with chromatin remodeling complexes (Kapoor and Shen, 2014;Serebryannyy et al, 2016) and the transcription factor MAL (Vartiainen et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, depleting nuclear actin through changes in growth factors or extracellular molecules has been reported to inhibit RNAPII activity, and this inhibition can be rescued by expressing NLS-R62D-β-actin (Spencer et al, 2011). These data, which support the notion that monomeric actin is important in maintaining transcription, are consistent with the previous demonstration that monomeric nuclear actin interacts with chromatin remodeling complexes (Kapoor and Shen, 2014;Serebryannyy et al, 2016) and the transcription factor MAL (Vartiainen et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…A recent study in epidermal stem cells also demonstrated that a reduced level of nuclear actin in response to mechanical stretch can lead to chromatin rearrangement and associated changes in H3K9Me3 and H3K27Me3 levels (44). In contrast, general chromatin decompaction may be a consequence of altered histone deacetylase (HDAC) activity in the absence of b-actin, given that nuclear actin has recently been described to interact with HDACs and to regulate their enzymatic activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, actin was identified as a functional binding partner of histone deacteylase (HDAC) 1 and 2 of the nucleosome remodeling histone deacetylase (NuRD) complex and the corepressor for element-1-silencing transcription factor (CoREST) complex (Serebryannyy et al, 2016a). Nuclear actin monomers bind HDACs and inhibit their function, whereas stimulation of nuclear actin polymerization alleviates this suppression (Serebryannyy et al, 2016a). HDACs remove acetyl-moieties from histones, relaxing chromatin and promoting transcription (Seto and Yoshida, 2014).…”
Section: Chromatin Organizationmentioning
confidence: 99%